Matrix Metalloproteinase-8 Augments Bacterial Clearance in a Juvenile sepsis Model - Sarah J Atkinson; Brian M Varisco; Mary Sandquist; Meghan N Daly; Lindsey Klingbeil; Joshua W Kuethe; Emily F Midura; Kelli Harmon; Amy Opoka; Patrick Lahni; Giovanna Piraino; Paul Hake; et al. (BMC, 2016)
Abstract Genetic ablation or pharmacologic inhibition of matrix metalloproteinase-8 (MMP8) improves survival in an adult murine sepsis model. Because developmental age influences the host inflammatory response, we hypothesized that developmental age influences the role of MMP8 in sepsis. First, we compared sepsis survival between wild-type (WT, C57BL/6) and MMP8 null juvenile-aged mice (12-14 d) after intraperitoneal injection of a standardized cecal slurry. Second, peritoneal lavages collected 6 h and 18 h after cecal slurry injection were analyzed for bacterial burden, leukocyte subsets and inflammatory cytokines. Third, juvenile WT mice were pretreated with an MMP8 inhibitor prior to cecal slurry injection; analysis of their bacterial burden was compared with vehicle-injected animals. Fourth, the phagocytic capacity of WT and MMP8 null peritoneal macrophages was compared. Finally, peritoneal neutrophil extracellular traps (NETs) were compared using immunofluorescent imaging and quantitative image analysis. We found that juvenile MMP8 null mice had greater mortality and higher bacterial burden than WT mice. Leukocyte counts and cytokine concentrations in the peritoneal fluid were increased in the MMP8 null mice relative to the wild-type mice. Peritoneal macrophages from MMP8 null mice had reduced phagocytic capacity compared to WT macrophages. There was no quantitative difference in NET formation, but fewer bacteria were adherent to NETs from MMP8 null animals. In conclusion, in contrast to septic adult mice, genetic ablation of MMP8 increased mortality following bacterial peritonitis in juvenile mice. This increase in mortality was associated with reduced bacterial clearance and reduced NET efficiency. We conclude that developmental age influences the role of MMP8 in sepsis.